Microencapsulation of Ducrosia anethifolia essential oil: Optimization characterization, and stability - Azita Shafiei; Javad Safaei-Ghomi; Reihaneh Masoomi (Applied Food Research)
In this study, encapsulation of Ducrosia anethifolia essential oil (DEO) was evaluated using maltodextrin, gum Arabic, starch, inulin, and gelatin with different ratios. The wall ratio, the amount of total solid, essential oil, and the spray dryer temperature were also optimized. Microparticles produced under optimum criteria containing maltodextrin, gum Arabic, gelatin (28:8:4) had an encapsulation efficacy of 90.97 %. Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), and thermal analysis demonstrated that DEO was appropriately encapsulated in the matrix wall. GC/MS analysis revealed that DEO compounds were preserved after encapsulation. The stability results showed that loss of DEO from microcapsule during accelerated and real-time stability is lower than 9 % and 1.5 %, respectively. The release mechanism of DEO from microparticles was studied using first-order, Korsmeyer-Peppas, Peppas-Sahlin, and Higuchi models. Peppas-Sahlin model showed the best-fit to investigate the release kinetics, also the model indicated that the release mechanism is mostly done through diffusion. Considering the successful encapsulation of DEO, high stability, and sustained release, it can be applied in the pharmaceutical and food industries.